The Influence Of Work Dicipline And Safety On The Employess Of The Cutting Section At PT Adis Dimension Footwear,Tangerang Regency - Lestari, Khoiriyah; Yulandari, Sri; Setiawan, Temmy (UJoST- Universal Journal of Science and Technology, 2026)
This study aims to determine: (1) the partial effect of work discipline on employee performance; (2) the partial effect of work safety on employee performance; (3) the simultaneous effect of work discipline and work safety on employee performance.This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all production employees at PT. Adis Dimension Footwear Balaraja- Tangerang. The research sample consisted of 133 respondents, and the sampling technique used was simple random sampling. The Slovin formula was used to determine a representative sample size in quantitative research. Data analysis used multiple linear regression analysis with SPSS 26.The results of this study indicate that (1) partially, work discipline significantly influences the performance of employees in the Cutting department at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (2.191>1.978) and a significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work safety significantly influences the performance of employees in the Cutting section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (8.195>1.978) and a significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, work discipline and work safety significantly influence the performance of employees in the Cutting section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (66.452>3.07) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that the variables of work discipline and work safety, both partially and simultaneously, have a significant influence on the performance of employees in the Cutting department at PT. Adis Dimension Footwear Balaraja-Tangerang.